E-learning Quality Assessment Indicators: A Narrative Review - Fatemeh Sadeghi; Somayeh fazaeli; Khalil kimiafar; Fatemeh Ameri; Marziyhe Meraji (Journal of Medical Education and Development, 2024)
Introduction: Due to the widespread use of this educational method in the universities of the world and Iran, there is a need to evaluate its quality using indicators and approaches. Therefore, the present study was conducted to evaluate the quality evaluation indicators of electronic education. Method: The present study was conducted according to the guidelines of PRISMA. For this purpose, Web of Science, PubMed, Scopus, Mogiran, Irandak and SID databases were searched in the period from 2018 to 2022. The search strategy included the concepts of "e-learning", "index" and "medical science students". The criteria for entering this study were original articles in Persian and English. After selecting the studies, data collection was done based on the data extraction form. Results: A total of 77 articles were included in this review. From the review of studies, 37 indicators in 6 categories of factors related to students (5 indicators), factors related to professors (11 indicators), factors related to educational content (5 indicators), factors related to required facilities (7 indicators), factors related to Management (5 indicators) and factors related to laws and regulations (4 indicators) were obtained. Conclusion: The results showed that six factors are involved in evaluating the quality of e-learning. Therefore, it is recommended that the managers of the educational systems to ensure the provision of high-quality training by identifying the weaknesses of the electronic learning software system and laying the foundation for their elimination.